A Telemedicine Model to Improve and Facilitate Access to Healthcare: Online Polyclinic - Behçet Al; Saud Alturki; Emre Yalçıntaş; Eltaf Torun (Eurasian Journal of Emergency Medicine)
Significant congestion occurs in healthcare facilities worldwide, especially in hospitals. Turkey’s healthcare system has a notably higher patient density than other countries. This overcrowding is evident across all healthcare units, particularly emergency departments. A key reason is the mismatch between patients and healthcare systems, which leads to an imbalance between supply and demand. Each country seeks solutions to address this increasingly challenging problem within its resources. Finding and creating urgently needed solutions also falls under the responsibility of healthcare professionals. In this study, we propose a model that can alleviate congestion to reasonable and acceptable levels through an online clinic. This model offers a comfortable experience for healthcare providers and recipients without obstructing the patient’s need to see a physician. This unique method, the Online Polyclinic Model, leverages modern technological advancements to deliver a highly secure, accessible, and convenient healthcare service that reaches everyone, reducing healthcare costs without compromising quality while saving time and space. Patient density is often defined in the emergency department congestion literature. The examples in our study also primarily focused on emergency department congestion. However, the aim is to find a solution for congestion that affects the entire healthcare system.